1983
DOI: 10.1159/000145741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Retinoic Acid on the Development of the Facial Skeleton in Hamsters: Early Changes Involving Cranial Neural Crest Cells

Abstract: Treatment of gravid hamsters with 60 mg/kg of retinoic acid on the 8th day of pregnancy resulted in facial skeletal defects in 100% of the survivors examined by alizarin staining at term. An investigation of the early stages in the development of these malformations indicated that the teratogen induced delayed and disorganized patterns of cranial neural crest cell migration as well as extensive death and damage of crest cells. The results demonstrate that retinoic acid provides a useful tool for studies in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…These early theories included abnormal patterns of neural crest cell migration, 18 abnormal domains of cell death, 19,20 improper cellular differentiation during development 21 or an abnormality of the extracellular matrix; 22 however, there was little experimental evidence to support any of these hypotheses. The integration of molecular biology, cell biology, mouse genetics and experimental embryology has recently provided novel insights into the molecular pathogenesis of TCS.…”
Section: Molecular and Genetic Basis Of The Diseasementioning
confidence: 99%
“…These early theories included abnormal patterns of neural crest cell migration, 18 abnormal domains of cell death, 19,20 improper cellular differentiation during development 21 or an abnormality of the extracellular matrix; 22 however, there was little experimental evidence to support any of these hypotheses. The integration of molecular biology, cell biology, mouse genetics and experimental embryology has recently provided novel insights into the molecular pathogenesis of TCS.…”
Section: Molecular and Genetic Basis Of The Diseasementioning
confidence: 99%
“…In experimental animals, a Treacher-Collins(mandibu1o-facial dysostosis) like pattern occurred rather than a DiGeorge-like phenotype. Teratogenic doses of isotretinoin and vitamin A produced craniofacial malformations that closely resembled mandibulofacial dysostosis secondary to neural crest abnormalities (Poswillo, 1975;Sulik et al, 1987;Wiley et al, 1983).…”
Section: Mammalsmentioning
confidence: 97%
“…The evidence for a pathogenesis of retinoid teratogenicity resulting from an effect on neural crest migration and cell death (Webster et al, 1986;Wiley et al, 1983) provides a bridge to the studies of effects of isotretinoin on homeobox expression (Cho and DeRobertis, 1990). In experimental animals, a Treacher-Collins(mandibu1o-facial dysostosis) like pattern occurred rather than a DiGeorge-like phenotype.…”
Section: Mammalsmentioning
confidence: 99%
“…The analysis of Tcof1 heterozygous mice demonstrated that the correct dosage of treacle is essential for survival of cephalic neural crest cells that contribute significantly to formation of branchial arches. Hence, dysmorphogenesis of the lower face may be a consequence of defective neural crest cell migration from the hindbrain to the branchial arches during early embryogenesis (61,62). If the functions of hNop56p and treacle in ribosome biogenesis are directly related to TCS, then a possible underlying mechanism is that a sufficient supply of ribosomes is essential for normal development.…”
Section: Figmentioning
confidence: 99%